2013
DOI: 10.1038/tp.2013.64
|View full text |Cite
|
Sign up to set email alerts
|

Expression of GABAA α2-, β1- and ɛ-receptors are altered significantly in the lateral cerebellum of subjects with schizophrenia, major depression and bipolar disorder

Abstract: There is abundant evidence that dysfunction of the γ-aminobutyric acid (GABA)ergic signaling system is implicated in the pathology of schizophrenia and mood disorders. Less is known about the alterations in protein expression of GABA receptor subunits in brains of subjects with schizophrenia and mood disorders. We have previously demonstrated reduced expression of GABAB receptor subunits 1 and 2 (GABBR1 and GABBR2) in the lateral cerebella of subjects with schizophrenia, bipolar disorder and major depressive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
87
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 103 publications
11
87
2
Order By: Relevance
“…We found that Gabarapl1 expression was increased by chronic stress in the PFC and NAc, consistent with results in human MDD in which expression is increased in Brodmann area 9 (BA9), BA10, BA20, and BA46 [84, 85]. Consistent with what we observed for the effects of stress on Gabra2 expression in the PFC and NAc, subjects with MDD have increased Gabra2 expression in the cerebellum [86]. While single-nucleotide polymorphisms (SNPs) in the Gabbr2 gene are associated with MDD, human postmortem studies have not found altered expression of this gene in the brain (e.g., [85, 87]).…”
Section: Discussionsupporting
confidence: 88%
“…We found that Gabarapl1 expression was increased by chronic stress in the PFC and NAc, consistent with results in human MDD in which expression is increased in Brodmann area 9 (BA9), BA10, BA20, and BA46 [84, 85]. Consistent with what we observed for the effects of stress on Gabra2 expression in the PFC and NAc, subjects with MDD have increased Gabra2 expression in the cerebellum [86]. While single-nucleotide polymorphisms (SNPs) in the Gabbr2 gene are associated with MDD, human postmortem studies have not found altered expression of this gene in the brain (e.g., [85, 87]).…”
Section: Discussionsupporting
confidence: 88%
“…GABA A receptors are widely distributed in the brain and are the primary channels through which GABA inhibits the excitability of neurons in the central nervous system (24,25). Abnormalities in GABA function have been postulated for many years in bipolar disorder and are supported by the observation of decreased CSF GABA in bipolar patients (26), as well as alterations in GABA subunit ratios in the postmortem brain (27). Positive allosteric modulators of GABA A receptors (benzodiazepines) are used adjunctively in the treatment of mania, a key aspect of BD.…”
Section: Discussionmentioning
confidence: 99%
“…GABA A receptor subunit gene polymorphisms are differentially associated with risk for other mental disorders such as alcohol dependence (69), MDD, bipolar disorder and schizophrenia (70). In animal models, mice genetically designed to lack the δ subunit do not exhibit ALLO's paradoxical effects at the GABA A receptor during puberty as do wild-type mice (62).…”
Section: Introductionmentioning
confidence: 99%